Opportunities and challenges for the development of "core outcome sets" in neuro-oncology. Issue 7 (14th March 2022) - Millward, Christopher P; Armstrong, Terri S; Barrington, Heather; Brodbelt, Andrew R; Bulbeck, Helen; Byrne, Anthony; Dirven, Linda; Gamble, Carrol; Grundy, Paul L; Islim, Abdurrahman I; Javadpour, Mohsen; Keshwara, Sumirat M; et al.
Abstract: Core Outcome Sets (COS) define minimum outcomes to be measured and reported in clinical effectiveness trials for a particular health condition/health area. Despite recognition as critical to clinical research design for other health areas, none have been developed for neuro-oncology. COS development projects should carefully consider: scope (how the COS should be used), stakeholders involved in development (including patients as both research partners and participants), and consensus methodologies used (typically a Delphi survey and consensus meeting), as well as dissemination plans. Developing COS for neuro-oncology is potentially challenging due to extensive tumor subclassification (including molecular stratification), different symptoms related to anatomical tumor location, and variation in treatment options. Development of a COS specific to tumor subtype, in a specific location, for a particular intervention may be too narrow and would be unlikely to be used. Equally, a COS that is applicable across a wider area of neuro-oncology may be too broad and therefore lack specificity. This review describes why and how a COS may be developed, and discusses challenges for their development, specific to neuro-oncology. The COS under development are briefly described, including: adult glioma, incidental/untreated meningioma, meningioma requiring intervention, and adverse events from surgical intervention for pediatric brain tumors.